The effect of the deformation of the face throttle surface on the operation of the balancing disk of a multistage centrifugal pump - Tarasevych, Yuliia; Sovenko, Nataliia; Chronowska-Przywara, Kinga (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
This paper presents selected results of numerical and analytical analysis of a traditional design of an axial force balancing system in a multistage centrifugal pump. The value of the axial force generated in the face throttle of such a system is directly influenced by the geometry of the throttles: length and height. In the process of operating a multistage pump, the surfaces that form the face throttle are deformed due to high values of pressure or temperature. Changing geometry results in a change in the pressure distribution, and thus in the value of the generated axial force and hydraulic losses. The analytical approach provides a simplified theoretical estimation of disc deflection and force balance, while the numerical simulations capture the detailed pressure distribution and corresponding structural response for different face gap values. The practical value of this research lies in providing a deeper understanding of the relationship between balance disc deformation and axial force. The results enable more accurate selection of disc geometry and face gap value, helping to minimize residual thrust on bearings and hydraulic losses on the automatic balancing device.